Typology and Structure of the School Lesson: A Review of Publications before and after the Introduction of the 2nd Generation FGOS - BratashValentina S.; BysikNadezhda V.; VinogradovaYulia S. (Voprosy obrazovaniya / Educational Studies Moscow, 2025)
This article presents the results of an analysis of domestic scientific articles and teaching materials over the past 25 years, which are publicly available and address the topic of «lesson structure». An array of 65 publications was collected during work with electronic libraries: eLIBRARY.RU, CyberLeninka and the Google Academy, and covers the period from 1997 to 2022. The review includes four areas: description of current typologies of lessons, identification of features of the structure of educational classes, an explanation of what characterizes the concept of “modern lesson” in different time periods, as well as a generalization of the author’s approaches to lesson planning. The study of the collected materials made it possible to identify changes in the planning, organization and delivery of the lesson, as well as the interaction between the teacher and students. The role of the teacher has transformed from a keeper of knowledge to a source of motivation and mentor. Much attention begins to be paid to the student’s subjectivity and the development of his educational independence. In this regard, the interaction between teacher and student takes on a more partnership-like character. The lesson ceases to be considered as a separate event and becomes part of the system of training sessions and a unified educational process, and the structure of the lesson is revised taking into account the emotional involvement of students and the importance of achieving educational results.